The Subjective Experience of Joblessness in Poland - Tomescu-Dubrow, Irina; Dubrow, Joshua Kjerulf; Kiersztyn, Anna.; Andrejuk, Katarzyna; Kołczyńska, Marta; Slomczynski, Kazimierz M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book describes the experience of joblessness and unemployment in contemporary Poland. It does so by combining qualitative and quantitative data from a special project conducted in Poland after the Great Recession and the long-term Polish Panel Survey (POLPAN) to describe the lives of the jobless: women and men currently out of work, the recently re-employed, and housewives. The book uses a class and inequality perspective to investigate how these women and men became jobless, how they look for and find employment, their household and social activities, and their political participation. It contextualizes these experiences with a description of Poland's economy, labor market and employment policies after the fall of Communism and builds on the active interviewing and social constructionist approaches to explore the complex interviewer-respondent relationship.
Preface -- Introduction -- Part I. Background of the Study -- Chapter 1. The Experience of Joblessness: A Review of the Literature -- Chapter 2. Joblessness in Poland since 1989: Policies and Economic Situation -- Chapter 3. The Respondents, The Interviewers and the Interview Situation -- Part II. Routes into Joblessness -- Chapter 4. How I Became Unemployed -- Chapter 5. How I Became a Housewife -- Part III. Routes Out of Joblessness -- Chapter 6. Future Jobs -- Chapter 4. Looking for, and Finding a Job -- Part IV. Daily Life of the Jobless -- Chapter 8. Informal Jobs and Life at Home -- Chapter 9. Social and Political Activities of the Jobless -- Chapter 10. Conclusion -- Appendix A. Details about the Data and the Fieldwork Methodology -- Appendix B. The Survey Instrument.
Keywords: Social structure; Equality; Labor economics; Quality of life; Social Structure; Labor Economics; Quality of Life Research